The Effect of Ecotourism and Tourism Service Quality on Tourist Satisfaction on Failonga Island, Tidore Islands City - Ade, Widyawati; Tumbel, Tinneke M; Walangitan, Olivia (Productivity, 2024)
This research aims to determine the influence of ecotourism and tourism services on tourist satisfaction on Failonga Island, Tidore City, Archipelago. This research uses quantitative methods with the Multiple Linear Regression Analysis method. Testing simultaneously (t test) and simultaneously (F test) using SPSS software. The population in this study were people who had visited Failonga Island, Tidore City, Archipelago. Using the Lemeshow formula, a sample of 100 people was obtained. Based on the regression equation, it shows that the Ecotourism variable has a positive effect of 0.147 and Service Quality has a positive effect of 0.072. Based on the partial t test, Ecotourism has no significant effect on the dependent variable, namely (Y) Tourist Satisfaction.